Within-child associations between sleep quality and emotional self-regulation over 6 months among preschool-aged (3- to 5-year-old) children - Godzik, Cassandra M.; Carlson, Delaina D.; Pashchenko, Oleksandra I.; Ballarino, Grace A.; Emond, Jennifer A. (Frontiers in Sleep, 2024)
Objective We leveraged an observational, repeated-measures study to examine the within-child associations between sleep quality and emotional self-regulation, controlling for between-child effects. Methods Children aged 3–5 years and one parent each were recruited from the community in northern New England between 2019 and 2022. Parents completed online surveys at baseline and 2, 4, and 6 months post-baseline. Child sleep quality was measured with the validated Children's Sleep Habits Questionnaire modified for preschoolers; higher scores indicate worse sleep quality (range 32–96). Child emotional self-regulation was measured with the validated Child Social Behavior Questionnaire; higher scores indicate better emotional self-regulation (range 1–7). Adjusted mixed-effects linear regression was used to model the associations between nighttime sleep quality (exposure) and emotional self-regulation (outcome) measured at each of the four study time points while disaggregating the between- and within-child effects. Results Children (n = 91) were largely white, non-Hispanic (88.7%), and from a higher social-economic status. Sleep quality scores averaged 38.9 (SD: 6.6) at baseline; 23.1% of children had scores >41, which is considered evidence of significant sleep problems. Emotional self-regulation scores averaged 4.2 (SD: 1.0). There was a significant within-child association between sleep quality and emotional self-regulation. Specifically, a decrease in sleep quality at any one time point, relative to each child's mean sleep quality, related to worse emotional self-regulation [standardized beta, βs = −0.31; 95% CI (0.53, −0.09)]; the between-child effect was not significant. Results were consistent when limited to children with complete data at all study visits (n = 78). Conclusions The findings support a causal, within-child association between sleep quality and emotional self-regulation in preschool-aged children, with effects evident over 6 months.